공사장 가림막의 특성과 시각적 표현 유형의 선호도에 관한 연구 - 바이옌; Bai Yan; 이홍; Lee Hong; 안병진; Ahn Byoung Jin (기초조형학연구, 2018)
최근 각 지자체에서는 쾌적한 도시환경 조성을 위하여 도심에서 방치 된 시각적 공해요소로 전락해 온 공사장 가림막에 다양한 디자인적 시도를 통해 도심의 미관을 개선하고자 노력하고 있다. 특히 공사장 가림막에 대한 도시민들의 인식개선을 위해서, 이들이 선호하는 공사장 가림막 디자인은 무엇인지, 그리고 어떠한 유형을 선호하는지에 대하여 살펴볼 필요가 있다. 본 연구는 공사장 가림막 디자인의 인식, 시각적 표현요소와 특성요소에 대한 선호도 차이를 분석한 연구이다. 부산광역시에 거주하는 100명을 대상으로 2017년 6월 9일부터 30일 까지 설문 조사를 실시하였으며, 그중 중복체크 및 피실험자 조건을 성립하지 못하는 10부를 제외한 90부를 분석하였다. 본 연구의 분석 결과 공사장 가림막에 대한 인식은 전체 응답자의 87%가 가림막이 무엇인지에 대하여 알고 있었으며, 특히 연령대가 낮은 여성일수록 공사장 가림막 디자인에 대한 관심이 높은 것으로 조사되었다. 공사장 가림막디자인의 시각적 표현요소는 비대칭 레이아웃과 타이포와 이미지가 혼용된 디자인을, 배경이 있고 난색 위주와 모노 듀오톤의 색채를 선호하는 것으로 조사되었다. 공사장 가림막의 구성 요소 중에서 추상적 이미지와 사진 및 일러스트레이션 이미지가 주를 이루는 디자인을 선호하는 것으로 나타났다. 또한 대부분의 응답자가 공사장 가림막 디자인의 특성요소 중 기능성을 가장 선호하는 것으로 조사 되었다. 본 연구에서 공사장 가림막에 대한 인식, 가림막 디자인의 시각적 표현요소와 특성요소에 대한 선호도를 살펴보았으며, 공사장 가림막에 대한 고정관념과 인식에 대하여 개선하는데 도움이 되고자 하며, 또한 쾌적하고 심미적인 도시환경조성에 있어서 본 연구가 기초자료로 활용되길 희망한다. Recently, local governments try to improve the beauty of the city through various design attempts at construction fence that have become a visual pollution element left unattended in the downtown area to create pleasant urban environments. Especially, to improve the city's perception of construction fence, it is necessary to look at their preferred desing of construction fence, and the type of construction fence they prefer. This study is to analyze the perception of the construction fence, differences of preference of visual expressive elements and Characteristics elements. A questionnaire survey was conducted for 100 people living in Busan Metropolitan City from June 9 to 30, 2017, and 90 copies except for 10 copies which failed duplicate check and test subject condition. Analysis result 87% of respondents know the construction fence, especially the lower age female group be investigated the higher the interest in the design of construction fence. The visual expressive elements of the design of the construction fence prefer the asymmetric layout design and the design which the typography and the image mixed, the background, the warm color and the mono duotone color. Among the components of the construction fence, mainly design preferred which abstract images, photographs and illustration images. Also, most of the respondents were found to prefer the functionality among the characteristics of the design of the construction fence. Finally, this study examined the perception of the construction fence, differences of preference of visual expressive elements and Characteristics elements of the construction fence, It is expected that the result of this study will be useful as a basic data in the design of the construction fence in future.